Floral Transcriptome Analyses of Four Paphiopedilum Orchids with Distinct Flowering Behaviors and Development of Simple Sequence Repeat Markers - Dong-Mei Li; Wei Wu; Di Zhang; Xiao-Rong Liu; Xiao-Fei Liu; Yi-Jian Lin (Plant Molecular Biology Reporter, 2015)

The effects of grafting on glycolysis and the tricarboxylic acid cycle in Ca(NO3)2-stressed cucumber seedlings with pumpkin as rootstock - Lin Li; Wen-wen Xing; Qiao-sai Shao; Sheng Shu; Jin Sun; Shi-rong Guo (Acta Physiologiae Plantarum, 2015)

Simulation of salinity variability and the related freshwater flux forcing in the tropical Pacific: An evaluation using the Beijing normal university earth system model (BNU-ESM) - Hai Zhi; Rong-Hua Zhang; Pengfei Lin; Lanning Wang (Advances in Atmospheric Sciences, 2015)

The inward-rectifying K+ channel SsAKT1 is a candidate involved in K+ uptake in the halophyte Suaeda salsa under saline condition - Hui-Rong Duan; Qing Ma; Jin-Lin Zhang; Jing Hu; Ai-Ke Bao; Li Wei; Qian Wang; Sheng Luan; Suo-Min Wang (Plant and Soil, 2015)

Sinomonas halotolerans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Lin Meng; Jian-Rong Huang; Yan-Yan Duan; Shan-Hui Li; Shuai Li; Jian-Xin Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Quantitative analysis of the feedback induced by the freshwater flux in the tropical Pacific using CMIP5 - Hai Zhi; Rong-Hua Zhang; Pengfei Lin; Lanning Wang (Advances in Atmospheric Sciences, 2015)

Interlocking Intramedullary Nails in Fracture Treatment - Xiao Ouyang; Jing Rong Wang; Shi Dong Hong; Feng Xin; Lin Wang; Xiao Wei Yang; Jian Wang (Cell Biochemistry and Biophysics, 2015)

Paleoenvironments of the evolving P liocene to early P leistocene foreland basin in northwestern T aiwan: An example from the D ahan R iver section - Tsun‐You Pan; Andrew Tien‐Shun Lin; Wen‐Rong Chi (Island Arc, 2015)
The overriding of the L uzon volcanic arc atop the underlying C hinese rifted‐continental margin has caused the formation of the T aiwan mountain belts and a peripheral foreland basin west of the orogen since the late Miocene. In this study, lithofacies analysis and calcareous nannofossil biostratigraphic investigations of the Dahan River section in northwestern ( NW ) T aiwan were performed. Our results offer insights into the temporal evolution of the sedimentary environments and the competing effects of the sedimentation and basin tectonics of the NW T aiwan foreland basin from the P liocene to early P leistocene. Nannofossil biostratigraphic studies showed that the upper K ueichulin F ormation and the overlying C hinshui S hale can be assigned to the NN 15 biozone of the P liocene age, and the C holan F ormation pertains to NN 16– NN 18 of the early P leistocene. The NN 15– NN 16 boundary coincides roughly with the boundary of the C hinshui S hale and C holan F ormation. We recognized three major sedimentary environments in the studied foreland succession comprising the upper K ueichulin F ormation, C hinshui S hale, C holan F ormation and Y angmei F ormation, in ascending order. During the deposition of the upper K ueichulin Formation in the early P liocene, the dominant environment was a wave‐ and tide‐influenced open marine setting. During the late P liocene, the environment deepened to an outer‐offshore setting when the sediments of C hinshui Shale were accumulated. In the P leistocene, the environment then shallowed to wave‐dominated estuaries during the deposition of the lower C holan F ormation, and the basin was rapidly filled, generating a meandering and sandy braided river environment during the deposition of the upper C holan to the Y angmei Formation. In summary, the evolution of sedimentary environments in the studied succession shows a deepening then a shallowing and coarsening upward trend during the period from the Pliocene to the Pleistocene, spanning the age from approximately 4 to 1 Ma.

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

The bioavailability and adverse impacts of lead and decabromodiphenyl ether on soil microbial activities - Lei Chen; Wei Zhang; Rong Zhang; Kuangfei Lin; Lei He; Liqun Wu (Environmental Science and Pollution Research, 2015)

Selenium geochemical distribution in the environment and predicted human daily dietary intake in northeastern Qinghai, China - Dasong Yu; Dongli Liang; Lingming Lei; Rong Zhang; Xiaofeng Sun; Zhiqing Lin (Environmental Science and Pollution Research, 2015)

High immune activation and abnormal expression of cytokines contribute to death of SHIV89.6-infected Chinese rhesus macaques - Ren-Rong Tian; Ming-Xu Zhang; Lin-Tao Zhang; Xiao-Liang Zhang; Hong-Yi Zheng; Lin Zhu; Wei Pang; Gao-Hong Zhang; Yong-Tang Zheng (Archives of Virology, 2015)

Multiple Mesozoic magma processes formed the 240–185 Ma composite Weishan pluton, South China: evidence from geochronology, geochemistry, and Sr-Nd isotopes - Xing Ding; Wei-Dong Sun; Wei-Feng Chen; Pei-Rong Chen; Tao Sun; Sai-Jun Sun; Chiou-Ting Lin; Fu-Kun Chen (International Geology Review, 2015)

Host shoot clipping depresses the growth of weedy hemiparasitic Pedicularis kansuensis - Xiao-Lin Sui; Wei Huang; Yun-Ju Li; Kai-Yun Guan; Ai-Rong Li (Journal of Plant Research, 2015)

Molecular characterization of a transcriptionally active Ty1/copia-like retrotransposon in Gossypium - Yuefen Cao; Yurong Jiang; Mingquan Ding; Shae He; Hua Zhang; Lifeng Lin; Junkang Rong (Plant Cell Reports, 2015)

Organochlorine pesticides and their metabolites in human breast milk from Shanghai, China - Dasheng Lu; Dongli Wang; Rong Ni; Yuanjie Lin; Chao Feng; Qian Xu; Xiaodong Jia; Guoquan Wang; Zhijun Zhou (Environmental Science and Pollution Research, 2015)

Study on the Mechanisms of Cartilage Tissue Damage Caused by Hydrogen Peroxide - Xiao Ouyang; Bo Wei; Shi Dong Hong; Jing Rong Wang; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Nucleotide composition bias and codon usage trends of gene populations in Mycoplasma capricolum subsp. capricolum and M. agalactiae - XIAO-XIA MA; YU-PING FENG; JIA-LING BAI; DE-RONG ZHANG; XIN-SHI LIN; ZHONG-REN MA (Journal of Genetics, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Isolation and the interaction between a mineral-weathering Rhizobium tropici Q34 and silicate minerals - Rong Rong Wang; Qi Wang; Lin Yan He; Gang Qiu; Xia Fang Sheng (World Journal of Microbiology and Biotechnology, 2015)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

Polycyclic aromatic hydrocarbons associated with total suspended particles and surface soils in Kunming, China: distribution, possible sources, and cancer risks - Xiaoxia Yang; Dong Ren; Wenwen Sun; Xiaoman Li; Bin Huang; Rong Chen; Chan Lin; Xuejun Pan (Environmental Science and Pollution Research, 2015)

Baseflow characteristics in alpine rivers — a multi-catchment analysis in Northwest China - Rong Gan; Lin Sun; Yi Luo (Journal of Mountain Science, 2015)

Gene knockout of glutathione reductase 3 results in increased sensitivity to salt stress in rice - Tsung-Meng Wu; Wan-Rong Lin; Ching Huei Kao; Chwan-Yang Hong (Plant Molecular Biology, 2015)

Association analyses of FGFR2 gene polymorphisms with femoral neck bone mineral density in Chinese Han population - Shan-Shan Dong; Tie-Lin Yang; Han Yan; Zheng-Qin Rong; Jia-Bin Chen; Ruo-Han Hao; Xiao-Feng Chen; Yan Guo (Molecular Genetics and Genomics, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Modification and simulation of Rhizomucor miehei lipase: the influence of surficial electrostatic interaction on enantioselectivity - Gang Xu; Xiao Meng; Lin-Jie Xu; Li Guo; Jian-Ping Wu; Li-Rong Yang (Biotechnology Letters, 2015)

Identification of microRNAs and their target genes in Alport syndrome using deep sequencing of iPSCs samples - Wen-biao Chen; Jian-rong Huang; Xiang-qi Yu; Xiao-cong Lin; Yong Dai (Journal of Zhejiang University-SCIENCE B, 2015)

Protective effects of hydroxysafflor yellow A (HSYA) on alcohol-induced liver injury in rats - Yanhao He; Qiang Liu; Yanxiang Li; Xiaofeng Yang; Weirong Wang; Tingting Li; Wei Zhang; Yuexin Cui; Chaoyun Wang; Rong Lin (Journal of Physiology and Biochemistry, 2015)

Esthetic Management of Mucogingival Defects After Excision of Epulis Using Laterally Positioned Flaps - Yu-feng Xie; Rong Shu; Jie-lei Qian; Zhi-kai Lin; Georgios E. Romanos (Cell Biochemistry and Biophysics, 2015)

Rapid and simultaneous detection of three major diarrhea-causing viruses by multiplex real-time nucleic acid sequence-based amplification - Qiu-Hua Mo; Hai-Bo Wang; Hui-Rong Dai; Ji-Can Lin; Hua Tan; Qi Wang; Ze Yang (Archives of Virology, 2015)

Genome-wide investigation and transcriptome analysis of the WRKY gene family in Gossypium - Mingquan Ding; Jiadong Chen; Yurong Jiang; Lifeng Lin; YueFen Cao; Minhua Wang; Yuting Zhang; Junkang Rong; Wuwei Ye (Molecular Genetics and Genomics, 2015)

Halovenus rubra sp. nov., Isolated from Salted Brown Alga Laminaria - Dong Han; Wen-Jiao Zhang; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2015)